The Influence of Compensation on Job Satisfaction: A Literature Review from an Industrial Psychology Perspective - Ahmad Husnul Khotimah; Ajju Setyanto Tamsir; Raditya Anugrah Al Miftah; Rupus Rupus (Yayasan Edukasi Cakrawala Nusantara, 2025)
This study explores the relationship between compensation and job satisfaction from an Industrial Psychology perspective using a literature review method. Secondary data were drawn from scientific articles, academic papers, and research reports published between 2020 and 2025 in national and international journals. The analysis applied content analysis by identifying key variables, grouping findings, comparing results across sectors and regions, and synthesizing them based on the Equity Theory, Expectancy Theory, Herzberg’s Two-Factor Theory, and Social Exchange Theory. The review of seven studies shows that both financial compensation (salary, allowances, bonuses, incentives) and non-financial compensation (recognition, promotion opportunities, facilities) generally have a positive effect on job satisfaction. The extent of this effect varies according to contextual factors such as work environment, organizational culture, career development, and labor policies. Effective compensation policies should balance financial and non-financial rewards while aligning with employee expectations and organizational conditions. The study is limited by its reliance on secondary data and a restricted publication period.